Shimming toolbox: An open‐source software toolbox for B0 and B1 shimming in MRI. Issue 4 (28th November 2022) - D'Astous, Alexandre; Cereza, Gaspard; Papp, Daniel; Gilbert, Kyle M.; Stockmann, Jason P.; Alonso‐Ortiz, Eva; Cohen‐Adad, Julien
Abstract : Purpose: Introduce Shimming Toolbox ( https://shimming‐toolbox.org ), an open‐source software package for prototyping new methods and performing static, dynamic, and real‐time B0 shimming as well as B1 shimming experiments. Methods: Shimming Toolbox features various field mapping techniques, manual and automatic masking for the brain and spinal cord, B0 and B1 shimming capabilities accessible through a user‐friendly graphical user interface. Validation of Shimming Toolbox was demonstrated in three scenarios: (i) B0 dynamic shimming in the brain at 7T using custom AC/DC coils, (ii) B0 real‐time shimming in the spinal cord at 3T, and (iii) B1 static shimming in the spinal cord at 7T. Results: The B0 dynamic shimming of the brain at 7T took about 10 min to perform. It showed a 47% reduction in the standard deviation of the B0 field, associated with noticeable improvements in geometric distortions in EPI images. Real‐time dynamic xyz‐shimming in the spinal cord took about 5 min and showed a 30% reduction in the standard deviation of the signal distribution. B1 static shimming experiments in the spinal cord took about 10 min to perform and showed a 40% reduction in the coefficient of variation of the B1 field. Conclusion: Shimming Toolbox provides an open‐source platform where researchers can collaborate, prototype and conveniently test B0 and B1 shimming experiments. Future versions will include additional field map preprocessing techniques, optimization algorithms, and compatibility across multiple MRI manufacturers.